1980
DOI: 10.1139/o80-056
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for multiple forms of p-trifluoromethylbenzenesulfonyl-α-chymotrypsin

Abstract: p-Trifluoromethylbenzenesulfonyl-alpha-chymotrypsin, an analog of tosylchymotrypsin, has been prepared and shown to be stable enough to permit fluorine nuclear magnetic resonance experiments. Up to four distinct trifluoromethyl resonances can be observed for the modified protein at 94.1 MHz even when the enzyme derivative is prepared from protein which has been purified by several methods. The resonances observed appear to represent proteins which are grossly similar as regards molecular size and the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…It then follows that the two peaks originating from bound species in the 3TFMB spectra (Figures 2C and 4A) and 2TFMC (Figure 7B) each arise from two different binding modes within the same R 3 binding site, corresponding to two different chemical shift environments for the CF 3 group. Similar behavior has been reported for the binding of fluorinated ligands to other protein sites (23,26,32,35).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It then follows that the two peaks originating from bound species in the 3TFMB spectra (Figures 2C and 4A) and 2TFMC (Figure 7B) each arise from two different binding modes within the same R 3 binding site, corresponding to two different chemical shift environments for the CF 3 group. Similar behavior has been reported for the binding of fluorinated ligands to other protein sites (23,26,32,35).…”
Section: Discussionsupporting
confidence: 82%
“…In some instances, the individual peaks for bound species are clearly distinguishable (Figures 1, 2, 4-6, and 7E); in other instances, the broadened structure of the bound envelope is indicative of more than one peak in intermediate to slow exchange (Figures 3 and 7A,C). Gerig's laboratory has extensively documented similar behavior for the binding of fluorinated ligands to protein sites (23,25,(32)(33)(34)(35)(36). In our experiments, the bound resonances correspond to protein-ligand complexes with different chemical shifts, reflecting the high sensitivity of fluorine chemical shifts to small differences in microenvironment (24) (Figures 1-7), and these overlapping resonances can be decomposed into individual peaks by fitting to Lorentzianshaped transitions.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The intensity of the signal at 13.6 ppm in the spectra of native enzyme could be reduced by extended dialysis, ultrafiltration through UM-10 membranes, and various chromatographic steps, as described below. Similar observations have been made with [[4-(trifluoromethyl)phenyl]sulfonyl]--chymotrypsin (Ando et al, 1980), and in both cases we believe that the species represented by the fluorine chemical shift identical with that of the denatured enzyme represent a collection of autolysis products and possibly unreacted The first reporter group was placed on the enzyme by reaction of the native enzyme with the appropriate reagent. The second reporter group was placed on this modified enzyme with the conditions specified under Experimental Procedures.…”
Section: -(Trifluoromethyl)-a-bromoacetanilide Derivativesupporting
confidence: 85%
“…The chemical shift of this downfield component may have a pH dependence similar to that of the major peak, but better data will be required to establish this point quantitatively. The observation of this downfield feature is interesting because of the suggestion that acylchymotrypsin may have more than one active form (Wedler et al, 1975;Baggott & Klapper, 1976;Ando et al, 1980;MacClement et al, 1981). Shah and coworkers (1984) have recently reported that the NMR spectrum of the hemiacetal formed between 7V-acetyl-L-[l-13C]phenylalaninal and chymotrypsin displays two signals above pH 7, but not at lower pH.…”
Section: Discussionmentioning
confidence: 96%